Comparison of the effectiveness of the new generation dual wavelength laser with the conventional laser type in treating rabbit model temporomandibular joint osteoarthritis - Gizemnur Karadayı; Nihat Akbulut; Faik Alev Deresoy; Ahmet Altan (BMC Oral Health)
Abstract Background This study compared the effects of low-level laser applications with different wavelengths on rabbits' temporomandibular joint regeneration capacity with experimentally induced osteoarthritis. Methods This study used 23 male New Zealand white rabbits. The animals were randomly divided into three groups. Osteoarthritis was induced in all groups by injecting sodium monoiodoacetate into the rabbits' joints. The joints of the experimental animals in Group 1 (GRR laser-dual wavelength, n = 8) and Group 2 (Epic10 laser-conventional laser, n = 8) were treated with laser for 14 sessions. In the control group (n = 7), no treatment was performed after osteoarthritis was induced. After the end of laser therapy, the rabbits were sacrificed simultaneously, and the temporomandibular joints were removed. Defect filling percentage, osteochondral junction reconstruction, matrix staining, and cellular morphology were examined histopathologically. Results There was a connection between the groups with defect filling, and a statistically significant difference was found (p = 0.005). When we examined whether there was a connection between the osteochondral junction and the groups, it was determined that there was no statistically significant connection (p = 1.000). It was determined that there was a significant connection between the groups with matrix staining (p = 0.001). There was a connection between cellular morphology and the groups. It was determined that there was a statistically significant connection (p = 0.018). The defect filling, matrix staining, and cellular morphology values in both laser groups were better than in the control group. Conclusions Low-level laser therapy can increase remodeling and improve tissue repair in temporomandibular joint osteoarthritis treatment. There was no significant difference between lasers at different wavelengths in treating temporomandibular joint osteoarthritis.